Konkurencyjność polskich produktów mleczarskich na rynku Unii Europejskiej - Iwan, Bolesław (Polish Dairy Products' Competitiveness on the European Union Market, 2006)
Competition is one of the major characteristic of the market economy. Every sector aiming at development on the domestic and international market should define and strengthen its competitive advantages. The aim of the paper is to analyze some aspects of the Polish international trade of dairy products and to identify some aspects of competitiveness of these products on the international market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 321-327